DEVELOPING ENGLISH MATERIAL FOR CRUISE LINE BARTENDER FOR STUDENTS OF INTERNATIONAL BALI INSTITUTE OF TOURISM - Rahayu, Made Sri; Budasi, I Gede (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
This study aims to develop English for Cruise Line Bartender materials needed by Cruise Line Bartender students of The International Bali Institute of Tourism, to explain how the materials were developed, and to analyze the quality of the developed materials. This study adopts the design proposed by Dick and Carey (2001). The model proposed by Dick and Carey consists of several stages; 1) conducting need analysis (problem determination), 2) designing the model, 3) developing the model, 4) validating the model by experts, and 5) trying out the model (dissemination). The object of this study was the English for cruise line bartender at the International Bali Institute of Tourism. In collecting the data, three instruments were used namely questionnaires, guided interviews, and document analysis. The study shows that eight topics are required to be developed. The topics are getting to know you, setting up a bar, kinds of drink, drink recipe, and taking beverage order, we are sorry, cruise vacationers, and job interview. The materials were designed by following the English for Specific Purposes (ESP) material design involving input, content focus, language focus, and task. Since English for cruise line bartender is part of ESP that is under English for Occupational Purposes, the steps of the interactive data analysis method consist of data reduction, data display, and conclusion drawing. The results of expert judges' validation were analyzed descriptively by comparing the scores of two raters using Gregory's formula (2000). The quality of the developed materials was categorized as good material. Thus, it can be used as the source for learning by prospective the secretary of Cruise Line Bartender Program at The International Bali Institute of Tourism.Keywords: English Learning Materials, Cruise line, Bartender